Financial requirements for nationwide fibre access coverage - Stephan Jay; Thomas Plueckebaum (International Telecommunications Society (ITS), 2011)
It is common knowledge that Next Generation Access (NGA) networks require significant investments and that for many regions, especially in more rural areas, there is no viable business case. Taking note of the broadband strategies formulated by European governments the deployment cost is analysed to assess options for extending the profitable coverage of FTTH. In this paper a bottom-up cost model is applied to determine the investment and cost of deploying and operating a FTTH network in Germany on a national level. The monthly cost per subscriber at rising penetration is compared with the Average Revenue Per User (ARPU) to determine the required penetration level or the required revenue for profitable operation in a steady market state. Those regions for which there is no business case are analysed with regard to the level of required subsidies. All modelling is based on differentiated geotypes reflecting urban and rural areas. The basic cost model used has been applied to numerous case studies before and was adapted to determine different forms of subsidies. The research questions addressed are. What is the limit of profitable FTTH coverage in Germany? What is the level of prices, internal subsidisation or investment subsidy necessary to increase the coverage of FTTH in Germany? These results inform policy makers and operators of the relevant investment deltas and/or price levels needed to increase the coverage of next generation broadband access infrastructure.
Keywords: L96; L5; L51; 330; Next Generation Access; FTTH; cost modelling; GPON; P2P; broadband strategy